Beyond aesthetic consequences: congestive hepatopathy caused by pectus excavatum. (1st March 2018) - Baudouin, Robin; Levesque, Eric; Jancovici, René
Abstract: Pectus excavatum can lead to right ventricle compression. Although extremely rare, congestive hepatopathy should be considered when patients with severe pectus excavatum present with cardiovascular involvement.